Short-Term Rentals and the Residential Housing System: Lessons from Berlin - Crowe, Adam (Institute of Sociology of the Czech Academy of Sciences, 2021)
The increasing professionalisation of Airbnb-style short-term rentals has emerged within a grey space between residential housing and hotel accommodation. Subsequently, an array of contestations have arisen, due in no small part to the intangibility of online short-term rental platforms as well as the absence of clear regulation at the municipal level. In urban settings already confronted with housing issues such as supply shortages and reduced affordability, recent studies show how the proliferation of short-term rentals can amplify housing market pressure while feeding into the broader urban processes of gentrification, touristification, and displacement. Using Berlin, Germany, as a site of analysis, this paper explores the expansion of short-term rentals in relation to various policy interventions designed to regulate the conversion of residential housing into tourist accommodation.